2015
DOI: 10.1371/journal.pone.0123575
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of MicroRNA-223 Promotes Degranulation via the PI3K/Akt Pathway by Targeting IGF-1R in Mast Cells

Abstract: BackgroundMast cells play a central role in allergic and inflammatory disorders by inducing degranulation and inflammatory mediator release. Recent reports have shown that miRNAs play an important role in inflammatory response regulation. Therefore, the role of miR-223 in mast cells was investigated.MethodsThe expression of miR-223 was quantified by quantitative real-time polymerase chain reaction (qRT-PCR) in immunoglobulin E (IgE)-mediated mast cells. After successful miR-223 inhibition by transfection, degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…Interestingly, miR-223 is known to be involved in and specific to hematopoiesis and is important for granulocyte differentiation. Downregulation of miR-223 can promote degranulation in RBL-2H3 MCs [5]. Inhibition of MC degranulation by miR-21 was observed in another study [6], while miR-146a was involved in MC survival [7].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, miR-223 is known to be involved in and specific to hematopoiesis and is important for granulocyte differentiation. Downregulation of miR-223 can promote degranulation in RBL-2H3 MCs [5]. Inhibition of MC degranulation by miR-21 was observed in another study [6], while miR-146a was involved in MC survival [7].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, microRNAs are being investigated as potential mechanisms to regulate MC activation. For example, microRNA‐223 targets insulin‐like growth factor 1 receptor in MCs, promoting degranulation and decreasing the phosphoinositide 3‐kinase/protein kinase B pathway …”
Section: Discussionmentioning
confidence: 99%
“…We found that expression of this miRNA was reproducibly reduced in Dnmt3a KO mast cells compared with their WT counterparts, and such reduction could also indirectly contribute to the increased ability of Dnmt3a KO mast cells to degranulate in response to acute stimulation. Indeed, down-regulation of miR-223 was recently shown to promote mast cell degranulation in response to IgE stimulation (54).…”
Section: Dysregulated Dna Methylation Activity Leads To Increased Masmentioning
confidence: 99%